2014
DOI: 10.1177/0954008313520021
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyphenylsulfone containing imidazole group for gas separation membrane material

Abstract: In this work, a series of polyphenylsulfones containing imidazole group in the polymer chain (imPPSU) was successfully synthesized. The permeability of gases carbon dioxide (CO 2 ), nitrogen (N 2 ), oxygen (O 2 ), and helium through a series of imPPSUs was determined at 25 C and an upstream pressure of 1 atm. The effects of nitrogen-containing heterocyclic groups on permeability coefficient and selectivity for the gas pairs CO 2 /O 2 , CO 2 /N 2 , and O 2 /N 2 were discussed. The polymers containing imidazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…CO 2 -responsive materials typically contain amine-functional groups, such as tertiary amines, amidine, guanidine or imidazole, that have a tendency to react with CO 2 to form charged ammonium bicarbonate in an aqueous environment [ 23 , 24 , 25 ]. For example, Yu et al successfully achieved a series of imidazole-containing polyphenylsulfone membranes for gas separation that showed high selectivity towards CO 2 due to the strong interaction between CO 2 and the imidazole group [ 26 ]. Heldebrant et al synthesised and developed a series of guanidine-containing compounds that can efficiently capture and release CO 2 over multiple cycles without losing activity or selectivity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 -responsive materials typically contain amine-functional groups, such as tertiary amines, amidine, guanidine or imidazole, that have a tendency to react with CO 2 to form charged ammonium bicarbonate in an aqueous environment [ 23 , 24 , 25 ]. For example, Yu et al successfully achieved a series of imidazole-containing polyphenylsulfone membranes for gas separation that showed high selectivity towards CO 2 due to the strong interaction between CO 2 and the imidazole group [ 26 ]. Heldebrant et al synthesised and developed a series of guanidine-containing compounds that can efficiently capture and release CO 2 over multiple cycles without losing activity or selectivity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous solution, these functional groups react quickly with CO 2 to form carbamate-ammonium groups, which improves water solubility. Imidazole has the highest p K a value, and thus a stronger basic strength, than other functional groups, and can thereby promote the formation of highly stable imidazole ring–CO 2 complexes within the structure of a material . For instance, Yu and co-workers reported that imidazole-containing polyphenylsulfone membranes showed excellent selective CO 2 separation performance owing to the strong interaction between CO 2 and the imidazole groups within the membranes . Recently, our research team successfully synthesized the CO 2 -responsive imidazole-functionalized anticancer drug Rhodamine 6G (I-R6G).…”
Section: Introductionmentioning
confidence: 83%
“…30 For instance, Yu and coworkers reported that imidazole-containing polyphenylsulfone membranes showed excellent selective CO 2 separation performance owing to the strong interaction between CO 2 and the imidazole groups within the membranes. 31 Recently, our research team successfully synthesized the CO 2 -responsive imidazole-functionalized anticancer drug Rhodamine 6G (I-R6G). I-R6G exhibits reversible, stable, and controllable physical properties in aqueous environments upon CO 2 and nitrogen (N 2 ) bubbling and could thus significantly improve the selectivity, efficacy, and safety of chemotherapy drugs in cancer cells.…”
Section: ■ Introductionmentioning
confidence: 99%